ATTRIBUTIONAL FACTORS OF THE PSYCHOTHERAPEUTIC EFFECTIVENESS - Romero Moreno, Antonio Francisco (Anales de Psicología / Annals of Psychology, 2008)
The aim of this research is to analyze the attribution given by the psychotherapists on the responsible factors of the cure in the psychotherapeutic process when finding out if that fitted responsibility relies on the specific variables of the psychotherapy (especially on the approach and the techniques used) or on the so called common factors (variables of the patient, the therapist and the relation therapist-patient). With this aim, and through a wide of the answers of a population of psychotherapists to a questionnaire designed ad hoc, we will try to prove if the conclusions obtained in the investigation of the results and the therapeutic processes up to the moment are useful to modify the generalized opinion among the psychotherapists that the main responsible factor of the cure is the technique used, understanding it as a specific variable. Among the main conclusions obtained, we need to mention the fact that the therapist cannot infer a clear position towards the specific or common factors being the main responsible for the therapeutic change. Likewise, the therapists consider mostly and significantly that the different psychotherapeutic patterns do not have a similar effectiveness. We also observe different discrepancies among the conclusions reached by the psychotherapy research and those stated by the therapists analyzed. Research and action lines are proposed.